A Membrane‐Free Redox Flow Battery with Two Immiscible Redox Electrolytes. Issue 41 (19th July 2017) - Navalpotro, Paula; Palma, Jesus; Anderson, Marc; Marcilla, Rebeca
Abstract: Flexible and scalable energy storage solutions are necessary for mitigating fluctuations of renewable energy sources. The main advantage of redox flow batteries is their ability to decouple power and energy. However, they present some limitations including poor performance, short‐lifetimes, and expensive ion‐selective membranes as well as high price, toxicity, and scarcity of vanadium compounds. We report a membrane‐free battery that relies on the immiscibility of redox electrolytes and where vanadium is replaced by organic molecules. We show that the biphasic system formed by one acidic solution and one ionic liquid, both containing quinoyl species, behaves as a reversible battery without any membrane. This proof‐of‐concept of a membrane‐free battery has an open circuit voltage of 1.4 V with a high theoretical energy density of 22.5 Wh L −1, and is able to deliver 90 % of its theoretical capacity while showing excellent long‐term performance (coulombic efficiency of 100 % and energy efficiency of 70 %). Abstract : Without a membrane : The use of immiscible electrolytes makes possible the total removal of any membrane in a "proof‐of‐concept" battery. Moreover, the metallic pairs commonly used in redox flow batteries are replaced by organic molecules. The same molecule could be used in a symmetric battery design thanks to the different redox mechanisms occurring in each electrolyte.